A Computational Pitting Corrosion Model of Magnesium Alloys - Chang, Chia-Jung; Chang, Chih-Han; Hung, Tin-Kan (Frontiers in Bioengineering and Biotechnology, 2022)
Controlling the corrosion rate of implants to maintain mechanical properties during tissue healing is significant in developing magnesium alloys implants. Besides surface treatment and material properties, the study of geometric alteration and mechanical strength are also vital for implant development. In this study, we developed a three-dimensional model for semi-autonomous computational pitting corrosion. It is based on the Monte Carlo method modeling magnesium alloy implants towards clinical application. The corrosion probability is based on the number of exposed surfaces to saline and the oxidation characteristics of the elements. The computational results are well compared with the experiment measurement by micro-computed tomography (micro-CT) in 500 hours. Subsequently, the computational analysis is extended to 3000 hours of corrosion analysis. The 3D model appears promising to assist the development of biodegradable implants.